Gingival phenotype distribution in young Caucasian women and men – An investigative study. Issue 1 (11th November 2021) - Fischer, Kai R.; Büchel, Jasmin; Kauffmann, Frederic; Heumann, Christian; Friedmann, Anton; Schmidlin, Patrick R.
Abstract: Objectives: To evaluate the relationship between gingival phenotype and tooth location based on selected index teeth ("Ramfjord") and assess possible differences between women and men. Material and Methods: Thirty‐six women and 20 men voluntarily participated in this investigation with an average age of 23 years (min: 19; max: 37). Gingival phenotypes (GP) were assessed by transparency of a periodontal probe through the buccal gingival margin. Results: A comparable and similar GP on all index teeth was only found in seven out of the 56 subjects, that is, thin or thick only: Five participants (three male/two female) showed a uniform and constantly thick and two females a constantly thin GP. While the majority of molars (94.6%; p  = 0.006) showed a thick GP, premolars (61.6%; p  = 0.09) as well as incisors (70.5%; p  = 0.046) were predominantly categorized as thin. In addition, significantly thicker GP was in general observed for maxillary teeth ( p  = 0.001) but without differences between genders ( p  = 0.722). Conclusion: No constant GP can be expected within one dentition. The use of the "Ramfjord teeth" may serve as a quick overview and reliable method to screen GP distribution.